Pemodelan Pola Sedimentasi di Muara Cisadane untuk Mendukung Pengembangan Terpadu Pesisir Ibukota Negara - Mardi Wibowo; Hanah Khoirunnisa; Khusnul Setia Wardhani; Reni Wijayanti (Universitas Diponegoro, 2022)
NCICD is one of the national strategic programs to deal with coastal problems in Jakarta. One alternative structure to be built is WLP or known as coastal resort. As an initial step to make it happen, BAPPENAS plans to build a WLP pilot plan around the S. Cisadane estuary. One of the main considerations for designing the WLP layout is the process and pattern of sedimentation around the Cisadane estuary. Therefore, computational modeling of sediment transport around the Cisadane estuary was carried out for a period of 1 year (August 2020-July 2021). This modeling uses MIKE-21 module MIKE21/3 Integrated Models software which combines hydrodynamics and cohesive sediment transport models. Based on the results of this modeling, it is known that there are differences in sediment transport patterns in the west and east monsoons. During 1 year, changes in the thickness of the bottom sediment around the estuary of S. Cisadane ranged from -0.4 to 0.7 m with a mean of 0.086 m. Coastal reservoir design must take into the very dynamic sedimentation process around the Cisadane estuary. Pengembangan Terpadu Pesisir Ibukota Negara (PTPIN) merupakan salah satu program strategis nasional untuk menangani permasalahan pesisir di Jakarta. Salah satu alternatif struktur yang akan dibangun adalah WLP atau dikenal sebagai coastal reservoir. Sebagai langkah awal mewujudkannya BAPPENAS merencanakan membangun pilot plan WLP di sekitar muara S. Cisadane. Salah satu pertimbangan utama untuk mendesain layout WLP adalah proses dan pola sedimentasi di sekitar muara Cisadane. Oleh karena itu dilakukan pemodelan komputasi transpor sedimen di sekitar muara Cisadane selama kurun waktu 1 tahun (Agustus 2020-Juli 2021). Pemodelan ini menggunakan software MIKE-21 module MIKE21/3 Integrated Models yang menggabungkan model hidrodinamika dan transpor sedimen kohesif. Berdasarkan hasil pemodelan ini diketahui bahwa terdapat perbedaan pola transpor sedimen di musim barat dan musim timur. Selama 1 tahun, perubahan ketebalan sedimen dasar di sekitar muara S. Cisadane berkisar -0,4-0,7 m dengan rerata 0,086 m. Pola sedimentasi yang sangat dinamis harus mendapatkan perhatian khusus dalam merancang waduk lepas pantai.